Maintenance des systèmes tournants par analyse vibratoire - Hakmi Houari; Dakmoussi Boubakeur; HADJADJ Abdechafik (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE Département de génie mécanique, 2024)
The objective of system diagnosis is predictive maintenance in order to intervene early and in real time to avoid major damage which causes the malfunction of the systems and sometimes their total shutdown. In the wind system, although electrical failures are rare, mechanical failures are quite common and can be very frequent. One of the main causes of these mechanical failures is bearing failure. The latter consists of several organs which can be defective separately from each other. The objective of our work is to diagnose the faults caused by the different bearing parts of the rotor axis of the generator in a wind power system. The diagnostic method that we adopted in this work is based on the frequency analysis by FFT of the voltage produced in order to determine the different signatures of the defects caused by the bearing components of the rotor axis. This method represents an alternative to the method based on the presence of vibration sensors
Maintenance Industerielle